Story As a Media for Improving Students' Learning Outcomes in Indonesian Class IV SD Negeri Dukuhlo 01, Bulakamba Sub-District, Brebes Regency - Kartini, Kartini (Universitas Sebelas Maret, 2020)
The purpose of this study is to improve students' learning outcomes in Mapel Bahasa Indonesia Elementary School grade IV with fairytale media. The research conducted is class Action Research ( PTK) as many as three cycles, with each cycle consists of two meetings. The stages of each cycle are planning, implementation, observation and reflection. Each meeting is conducted pre test and post test to know the development of students. In cycle I students who completed after doing post tests by 60 % . In cycle II students completed after post-test by 80%. In cycle III students who completed after doing post tests by 90%. These results show that the medium of learning fairy tales in Indonesian subjects can improve the learning outcomes of grade 4 students at SD Negeri Dukuhlo 01 Bulakamba Subdistrict, Brebes.